Direct determination of load flow quantities from PQ injections: A new formulation. (July 2017) - Varwandkar, S.D.; Lin, Jeremy
Highlights: Computation steps are exact explicit equations of physical laws without iteration . No changes needed for non-convergence for ill-conditioned & highly loaded systems. Phase angles are calculated from power expressions. Concept of p-currents with their Pythagorean relation is a new contribution. All generators are treated on pa (no classification as slack bus and PV bus). Abstract: Direct solution procedures for linear circuits do not work with power system networks due to nonlinearity of bus power equations. Numerical approach therefore becomes indispensable. We propose a different formulation based on physical modeling in which load data are used as their reciprocals 1/(P-jQ), which also denote their rated voltage impedances. Generators are represented by real and reactive power injections, the latter is obtained from SCADA, or, guessed from earlier-day-same-time values, or, limiting values read from capability curves . A module is defined with one generator and the network. Nonlinear power equation is then directly solvable for injected currents. We invoke linear circuit laws and sum the energies (powers) injected by individual generators into the network to obtain desired solution. Explicit expressions for losses, line flows, voltages, and angles are derived. Iterations are not required. Slack bus is not needed. Cases unsolvable with conventional methods can be solved with ease using this novel approach. The method outperforms iterative procedures in terms of computation times and proves its suitability for online applications.